Antioxidant ability in diabetic rats. Role of vitamina E - Oré Valdivieso, R. (2000)
The antioxiclant action of vitamin E was analyzed, the vitamin being administered to diabetic rats, and the changes in glicemia, glycosilated hemoglobin (HbA1c) lipid peroxidation, total antioxidant, albumin and total proteins were evaluated. Four groups of rats were employed: I control II control plus vit E, III diabetics by streptozotocin, IV diabetic plus vit E. After 8 weeks of treatment with insulin (4 U/Kg weight) diabetic animals dosed with vit E improved their glicemia and their HbA1c level decreased. In diabetic and control groups that received vit E lipid peroxidation decreased 25%, compared with those who didn't receive the supplement. These findings suggest that vit E tends to improve glicemia, decrease the HbA1c levels and total antioxidants in diabetic groups.